(NtWOR^ESTWO t(B.(Nn(B.(NhRENNIKOWA(B.s - (N{EHONINA i(B.s ((NmOSKWAs (NkOMPOZITORs, 1991)
(NaWTOR W POPULQRNOJ FORME RASSKAZYWAET O TWOR^ESTWE SOWETSKOGO KOMPOZITORA RASPOLAGAQ EGO PROIZWEDENIQ PO VANRAM(B.s
Keywords: (NMONOGRAFIQs